Primary Female Urethral Carcinoma: Proposed Staging Modifications Based on Assessment of Female Urethral Histology and Analysis of a Large Series of Female Urethral Carcinomas. (December 2020) - Aron, Manju; Park, Sanghui; Lowenthal, Brett M.; Gupta, Sounak; Sahoo, Debashis; Cheville, John C.; Hansel, Donna E.
Abstract : Primary female urethral carcinoma is rare. Limited clinicopathologic information has hindered development of staging criteria in this disease. We analyzed 29 primary female urethral carcinoma resections from 3 academic medical centers to characterize histopathologic features, clinical outcomes, and applicability of current and a novel modified staging criteria. We complemented this analysis with review of fully embedded female autopsy urethras to detail anterior and posterior urethral wall histology. Primary female urethral carcinoma subtypes included urothelial carcinoma in situ (3/29, 10%), adenocarcinoma in situ (1/29; 3%), invasive urothelial carcinoma (13/29, 45%), clear cell carcinoma (5/29, 17%), adenocarcinoma not otherwise specified (4/29, 14%) and squamous cell carcinoma (3/29, 10%). Only 6/29 cases (21%) were originally assigned a stage at diagnosis. Using histologic landmarks specific to the female urethra, we modified existing eighth edition American Joint Committee on Cancer urethral staging to a histology-based female urethral carcinoma staging (UCS) system. UCS stages were defined as pTa/pTisUCS (noninvasive carcinoma), pT1UCS (subepithelial tissue invasion), pT2UCS (periurethral muscle invasion), pT3UCS (vaginal adventitia or surrounding fibrovascular tissue), and pT4UCS (anterior wall fibroadipose tissue or posterior vaginal wall). UCS staging was applicable to all cases and showed stepwise changes in disease recurrence with increasing stage and was statistically significant for disease-specific and overall survival in contrast to the American Joint Committee on Cancer staging system. This study of one of the largest cohort of primary female urethral carcinomas provides a modified histology-based staging system specific to female urethral anatomy that provides outcomes-related information, which may be further validated by larger multi-institutional studies.